Ben Delatour Scout Ranch - Stevens Fuels Treatment Funds - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2009)
Located in: Fort Collins office files. Ben Delatour Scout Ranch documentation related to Colorado State Forest Service Stevens Fuels Treatment Funds, years 2009 through 2010. Includes: grant application, reports, cost documentation, program payment requests, invoices, and map of related area.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado